UPLC-HRMS Analysis Revealed the Differential Accumulation of Antioxidant and Anti-Aging Lignans and Neolignans in In Vitro Cultures of Linum usitatissimum L - Bose, Shankhamala; Munsch, Thibaut; Lanoue, Arnaud; Garros, Laurine; Tungmunnithum, Duangjai; Messaili, Souhila; Destandau, Emilie; Billet, Kévin; St-Pierre, Benoit; Clastre, Marc; Abbasi, Bilal Haider; Hano, Christophe; et al. (Frontiers in Plant Science, 2020)
Over the last few decades, methods relating to plant tissue culture have become prevalent within the cosmetic industry. Forecasts predict the cosmetic industry to grow to an annual turnover of around a few hundred billion US dollars. Here we focused on Linum usitatissimum L., a plant that is well-known for its potent cosmetic properties. Following the a) establishment of cell cultures from three distinct initial explant origins (root, hypocotyl, and cotyledon) and b) selection of optimal hormonal concentrations, two in vitro systems (callus vs cell suspensions) were subjected to different light conditions. Phytochemical analysis by UPLC-HRMS not only confirmed high (neo)lignan accumulation capacity of this species with high concentrations of seven newly described (neo)lignans. Evaluation over 30 days revealed strong variations between the two different in vitro systems cultivated under light or dark, in terms of their growth kinetics and phytochemical composition. Additionally, antioxidant (i.e. four different in vitro assays based on hydrogen-atom transfer or electron transfer mechanism) and anti-aging (i.e. four in vitro inhibition potential of the skin remodeling enzymes: elastase, hyaluronidase, collagenase and tyrosinase) properties were evaluated for the two different in vitro systems cultivated under light or dark. A prominent hydrogen-atom transfer antioxidant mechanism was illustrated by the DPPH and ABTS assays. Potent tyrosinase and elastase inhibitory activities were also observed, which was strongly influenced by the in vitro system and light conditions. Statistical treatments of the data showed relationship of some (neo)lignans with these biological activities. These results confirmed the accumulation of flax (neo)lignans in different in vitro systems that were subjected to distinct light conditions. Furthermore, we showed the importance of optimizing these parameters for specific applications within the cosmetic industry.